Cholesterol Crystals Activate the NLRP3 Inflammasome in Human Macrophages: A Novel Link between Cholesterol Metabolism and Inflammation - Rajamäki, Kristiina (Public Library of Science, 2010)
BACKGROUND: Chronic inflammation of the arterial wall is a key element in the pathogenesis of atherosclerosis, yet the factors that trigger and sustain the inflammation remain elusive. Inflammasomes are cytoplasmic caspase-1-activating protein complexes that promote maturation and secretion of the proinflammatory cytokines interleukin(IL)-1β and IL-18. The most intensively studied inflammasome, NLRP3 inflammasome, is activated by diverse substances, including crystalline and particulate materials. As cholesterol crystals are abundant in atherosclerotic lesions, and IL-1β has been linked to atherogenesis, we explored the possibility that cholesterol crystals promote inflammation by activating the inflammasome pathway. PRINCIPAL FINDINGS: Here we show that human macrophages avidly phagocytose cholesterol crystals and store the ingested cholesterol as cholesteryl esters. Importantly, cholesterol crystals induced dose-dependent secretion of mature IL-1β from human monocytes and macrophages. The cholesterol crystal-induced secretion of IL-1β was caspase-1-dependent, suggesting the involvement of an inflammasome-mediated pathway. Silencing of the NLRP3 receptor, the crucial component in NLRP3 inflammasome, completely abolished crystal-induced IL-1β secretion, thus identifying NLRP3 inflammasome as the cholesterol crystal-responsive element in macrophages. The crystals were shown to induce leakage of the lysosomal protease cathepsin B into the cytoplasm and inhibition of this enzyme reduced cholesterol crystal-induced IL-1β secretion, suggesting that NLRP3 inflammasome activation occurred via lysosomal destabilization. CONCLUSIONS: The cholesterol crystal-induced inflammasome activation in macrophages may represent an important link between cholesterol metabolism and inflammation in atherosclerotic lesions.